Losses and Energy Backflows of the Fundamental Core Mode in Solid Core Micro Structured Optical Fibers - Andrey Pryamikov (Photonics)
This work discusses the behavior of transverse energy fluxes of the fundamental core mode of a holey fibers and a photonic band gap fibers when the polarization state of this mode changes. The behavior of the transverse component of the Poynting vector of the fundamental core mode is considered for both linear and elliptical polarization. It is demonstrated that despite the difference in the distribution of the Poynting vector stream lines in the cross section of the fibers for the two polarizations, the leakage loss level is maintained constant due to the forward and reverse energy flows in the radial direction. Differences in the level of leakage losses in different micro structured fibers arise from the vortex structure of the Poynting vector of the fundamental core mode.